CD44 mediated colon cancer targeting mutlifaceted lignin nanoparticles: Synthesis, in vitro characterization and in vivo efficacy studies - Siddiqui, Lubna; Hasan, Nazeer; Mishra, Pawan K; Gupta, Neha; Singh, Anu T; Madaan, Alka; Jaggi, Manu; Saad, Suma; Ekielski, Adam; Iqbal, Zeenat; Kesharwani, Prashant; Talegaonkar, Sushama (International journal of pharmaceutics, 2023)
Hyaluronic acid (HA) coated irinotecan loaded lignin nanoparticles (HDLNPs) were synthesized using ionic interaction method. Optimized nanoparticles were characterized for their active chemotherapeutic targeting potential to CD44 receptors overly-expressed on cancer cells. Blood component interaction studies supported hemocompatible nature of HDLNPs and also demonstrated their sustained plasma residence property. Cell anti-proliferation and mitochondrial depolarization studies on HT-29 cells suggest significantly (p < 0.01) improved chemotherapeutic efficacy of HDLNPs. In vitro cell based studies showed that nanoparticles have retained antioxidant activity of lignin that can prevent cancer relapse. In vivo biodistribution studies in tumor-bearing Balb/c mice confirmed improved drug localization in tumor site for longer duration. Tumor regression and histopathological studies indicated the efficacy ofligand-assisted targeting chemotherapy over the conventional therapy. Hematological and biochemical estimation suggested that irinotecan-associated myelosuppression, liver steatosis and rare kidney failure can be avoided by its encapsulation in HA-coated lignin nanoparticles. HDLNPs were found to be stable over a period of 12 months.
Keywords: Tissue Distribution; nádorové buněčné linie; Active targeting; antigeny CD44; lignin; Nanoparticles; Hyaluronan Receptors; Mice; Cell Line, Tumor; Antineoplastic Agents; Irinotecan; hyaluronan/CD44 receptors; nádory tračníku; kyselina hyaluronová; protinádorové látky; zvířata; tkáňová distribuce; Mitochondrial depolarization; Hyaluronic Acid; irinotekan; Colonic Neoplasms; nanočástice; Lignin nanoparticles; myši; Lignin; Hyaluronic acid; Solid tumor; Animals